Is Green Brand Knowledge Affected Green Purchase Intention on Instant Noodle Product in Bandung, Indonesia? - Susilawati, Erna; Nurdiarkoro, Hanif (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Everyone wants to be healthy, but they are sometimes tempted to eat junk food or instant food. It can be dangerous for their health if consumed for a long time. One of the most temptation’s food is instant noodles. This study aims to determine the effect of Green Brand Knowledge on Green Purchase Intention (Study on Lemonilo Organic Instant Noodle Consumers at Organic Store Bandung). This research is descriptive and verification research methods. The population in this study is conducted to 90 samples using the Slovin formula. The analytical method used in this research is the multiple linear regression analysis method. The results show that the Green Brand Knowledge significantly influence on Green Purchase Intention.